The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijerph19159378
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Lumbar Segmental Instability in Young Individuals with the Different Types of Lumbar Disc Herniation—Preliminary Report

Abstract: Lumbar segmental instability (LSI) can cause pain and disability, and its background can be related to lumbar disc herniation (LDH). This retrospective study was conducted to analyze the prevalence of lumbar segmental instability (LSI) in young patients with different types of lumbar disc herniation (LDH). The study evaluated 133 individuals (18–25 years old) who suffered from LDH and underwent MRI and flexion-extension X-rays. Two groups were created: protrusion (PRO) and extrusion (EXT). LSI was scored posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The majority of individuals experience at least one episode of acute LBP during their lifetime, with a considerable proportion transitioning into a chronic condition. Studies indicated that the prevalence of chronic LBP can reach as high as 57% [ 2 ]. It is intricately associated with lumbar segmental instability, encompassing intervertebral disc, ligament, facet joint, and muscle dysfunctions [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of individuals experience at least one episode of acute LBP during their lifetime, with a considerable proportion transitioning into a chronic condition. Studies indicated that the prevalence of chronic LBP can reach as high as 57% [ 2 ]. It is intricately associated with lumbar segmental instability, encompassing intervertebral disc, ligament, facet joint, and muscle dysfunctions [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sustained loading on the cervical spine, such as prolonged use of smartphones or computers, can lead to disc degenerative disease and forward head posture (FHP) [ 4 ]. Kuligowski T [ 5 ] found that the overall incidence of lumbar segment instability was higher with severer disc damage. FHP affects the length–tension relationship in the suboccipital muscles and causes structural and functional changes in the surrounding muscles, which result in suboccipital muscle dysfunction [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…LSI prevalence can be as high as 57% of patients with chronic LBP [ 5 ]. The LSI is related to the proper and balanced working of the three subsystems: active, passive, and neural control [ 6 ]. The abnormal function of one of them can lead to an overload of others and cause pain and reduced quality of life [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The abnormal function of one of them can lead to an overload of others and cause pain and reduced quality of life [ 7 ]. LSI symptoms might lead to spondylolisthesis [ 6 , 8 ]. However, LSI is difficult to define, whether or not spondylolisthesis is involved [ 9 ].…”
Section: Introductionmentioning
confidence: 99%